2019
DOI: 10.21608/ajar.2019.102643
|View full text |Cite
|
Sign up to set email alerts
|

Influence of silicon treatments on some growth, physiological and biochemical traits of five Egyptian wheat varieties

Abstract: In Egypt there is a big gap between production and consumption of wheat. Hydroponically experiment was conducted in a randomized complete block design with three replicates. The herein experiment was carried out to study the effect of silicon (Si) treatments (0, 25, 50 and 100 mg/L) on some growth parameters, physiological, biochemical traits, some nutrients and Si content on different plants parts in five Egyptian wheat varieties (Gemmeza 7, Gemmeza 9, Gemmeza 11, Masr 1 and Giza 168). The results showed enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In the first and the second seasons the highest mean values of number of pods /plant, number of seeds seed weight/ plant,100 seed weight, yield/feddan (ton), Protein percent, oil percent, chlorophyll a, chlorophyll b and carotin traits were recorded with S2×C2 interaction followed by S2×C1 well as the same combination recorded the lowest mean values of infestation pods and seeds with pod worm percent Table 3, Fi Fig. 2 [40] who found that it can be concluded that foliar nutrition introduced into production as treatment in the crop management species of agricultural plants. It can help farmers to increase the yield of crops.…”
Section: Fig 2 Interaction Effect Of Potassium Silicate and Cultivars On Protein And Oil Percent Inmentioning
confidence: 88%
“…In the first and the second seasons the highest mean values of number of pods /plant, number of seeds seed weight/ plant,100 seed weight, yield/feddan (ton), Protein percent, oil percent, chlorophyll a, chlorophyll b and carotin traits were recorded with S2×C2 interaction followed by S2×C1 well as the same combination recorded the lowest mean values of infestation pods and seeds with pod worm percent Table 3, Fi Fig. 2 [40] who found that it can be concluded that foliar nutrition introduced into production as treatment in the crop management species of agricultural plants. It can help farmers to increase the yield of crops.…”
Section: Fig 2 Interaction Effect Of Potassium Silicate and Cultivars On Protein And Oil Percent Inmentioning
confidence: 88%